PEMBERDAYAAN SENTRA BAHAN ALAM UNTUK MENGEMBANGKAN KECERDASAN NATURALIS ANAK USIA DINI DI TAMAN KANAK-KANAK ISLAM TERPADU NURUL ILMI KOTA JAMBI - Hafizotun, Latansa (Jurnal Al-Ashlah, 2017)
This study was conducted in Kindergarten Integrated Islam Nurul Ilmi Jambi aimed to describe about the empowerment center for natural materials, see the achievements of the development of naturalist intelligence implementation and evaluation of children and learning centers of natural materials.This study used a qualitative descriptive approach by taking the kindergarten setting Kindergarten Integrated Islam Terpadu Nurul Ilmi Jambi. Research subjects include all characteristics associated with natural ingredients as you approach the center of learning in early childhood. Subjects of this study consists of the principal, one teacher Sentra Nature Materials 1 teacher assistant in the class of natural materials and childrens centers B4 class centers of natural materials is composed of 20 children. And samples taken 3 children. Technique in this research is purposive sampling technique, the technique of sampling data sources with particular consideration. Data collected by observation, interview and documentation. Analysis of the data is done by summarizing the data, melilih basic things and focus on the important things and will be studied then make conclusions so easily understood.The results showed that 1) the planning empowerment centers of natural materials in Kindergarten Integrated Islam Nurul Ilmi Jambi to develop naturalist intelligence has not been prepared teacher does not describe specifically the type of intelligence plural which will be developed, should the learning objectives in the lesson plan has clearly stated wit plural which will distimulan so that teachers focus more on preparing for and conducting research pembalajaran 2) evaluation of the teachers have a goal to be able to see the results obtained by the childs development during the study. No form of special assessments to learning 3) empowerment center for natural materials to develop naturalist intelligence early childhood has not run optimally, because the learning activity center for natural ingredients is always carried out in the classroom, lack of means of educational games, teachers understanding of the learning center for natural materials still minimal 4) equipment in the center of the natural ingredients in Kindergarten Integrated Islam Nurul Ilmi Jambi still very minimal, so very influential on early childhood intelligence. Results of this study recommend to all providers of early childhood education centers in order to implement the empowerment of natural materials to develop naturalist intelligence children this age in order to develop optimally.Â Keyword: Kindergarten, Sentra Natural Materials and naturalist intelligence